THE INFLUENCE OF FINANCIAL STABILITY, EXTERNAL PRESSURE, AND INSTITUTIONAL OWNERSHIP ON FRAUD OF FINANCIAL REPORTS - Darmayanti, Novi; Muhajir, Ali; Bilgies, Ana Fitriyatul; Syaikhudin, Ahmad Yani; Irawan, Mohamad Rizal Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This study aims to examine and analyze how the influence of Financial Stability, External Pressure, and Institutional Ownership on Financial Statement Fraud (Empirical Study on Index LQ-45 Companies Listed on the Indonesia Stock Exchange for the Period 2017-2021). The research approach used is quantitative. The population in this study is Index LQ-45 Companies listed on the IDX for 5 consecutive years for the period 2017-2021. The sampling technique used purposive sampling and produced a sample of 70 samples from 14 companies. The data analysis technique used multiple linear regression analysis and hypothesis testing. The results of this study indicate that partially the Financial Stability variable has a negative influence on Financial Statement Fraud, External Pressure variable has a positive influence on Financial Statement Fraud, and Institutional Ownership variable has a positive influence on Financial Statement Fraud.